EFEKTIFITAS TAUMA HERBAL DRINK TERHADAP INTENSITAS DISMENOREA - Cia ' Novita; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstrak Every fertile woman will menstruate, which normally complain of symptoms of the first two days. The most common physicial symptom is dysmenorrhoea. This study was aimed to determine the effectiveness of Tauma herbal drink in intensity of dysmenorrhoea. The design of this research study was "Quasy experiment" with "Non-equivalent control group" which is divided into an experimental group and a control group. The study was conducted on student school of nursing, University of Riau. Total sample were30 students who fit the inclusion criteria and using simple purposive sampling technique. Measuring instruments are used sheets observasion numeric scale. The analysis used  univariate and bivariate analysis by independent sample t test and dependent sample t test. The results showed a decrease in the intensity of dysmenorrhoea in the experimental group after given Tauma herbal drink with p value (0.000) <α (0.05). This means that Tauma herbal drink was effective to reduce the intensity of dysmenorrhoea. Tauma herbal drink can reduce dysmenorrhea in non-pharmacological which can be practiced independently, so it was suggested to students who have other family members or neighbors can use complementary therapies to reduce pain intensity of dysmenorrhoea. Keywords: dysmenorrhoea, tauma herbal drink, menstruasion References: 40 (2002-2014)